MiR-137 is a tumor suppressor in endometrial cancer and is repressed by DNA hypermethylation. (November 2018) - Zhang, Wei; Chen, Jo-Hsin; Shan, Tianjiao; Aguilera-Barrantes, Irene; Wang, Li-Shu; Huang, Tim; Rader, Janet; Sheng, Xiugui; Huang, Yi-Wen
Abstract Endometrial cancer is the most common gynecological cancer in the United States. We wanted to identify epigenetic aberrations involving microRNAs (miRNAs), whose genes become hypermethylated in endometrial primary tumors. By integrating known miRNA sequences from the miRNA database (miRBase) with DNA methylation data from methyl-CpG-capture sequencing, we identified 111 differentially methylated regions (DMRs) associated with CpG islands (CGIs) and miRNAs. Among them, 22 DMRs related to 29 miRNAs and within 8 kb of CGIs were hypermethylated in endometrial tumors but not in normal endometrium.miR-137 was further validated in additional endometrial primary tumors. Hypermethylation ofmiR-137 was found in both endometrioid and serous endometrial cancer (P  < 0.01), and it led to the loss ofmiR-137 expression. Treating hypermethylated endometrial cancer cells with epigenetic inhibitors reactivatedmiR-137 . Moreover, genetic overexpression ofmiR-137 suppressed cancer cell proliferation and colony formation in vitro. When transfected cancer cells were implanted into nude mice, the cells that overexpressedmiR-137 grew more slowly and formed smaller tumors (P  < 0.05) than vector transfectants. Histologically, xenograft tumors from cancer cells expressingmiR-137 were less proliferative (P  < 0.05), partly due to inhibition of EZH2 and LSD1 expression (P  < 0.01) in both the transfected cancer cells and tumors. Reporter assays indicated thatmiR-137 targets EZH2 and LSD1. These results suggest thatmiR-137 is a tumor suppressor that is repressed in endometrial cancer because the promoter of its gene becomes hypermethylated. The authors aimed to identify epigenetic aberrations involving microRNAs (miRNAs) whose genes become hypermethylated in endometrial primary tumors. They found that that miR-137 is hypermethylated and loses expression in human endometrial tumors. Increasing miR-137 expression suppresses endometrial cancer cell growth in vitro and xenograft tumor growth in nude mice, partly because miR-137 targets EZH2, which participates in histone methylation, and LSD1, a histone demethylation enzyme.